Zinc phthalocyanine conjugated cellulose nanocrystals for memory device applications. (8th November 2021) - Chaulagain, Narendra; Alam, Kazi M; Kumar, Pawan; Kobryn, Alexander E; Gusarov, Sergey; Shankar, Karthik
Abstract: We present the electrical properties of zinc phthalocyanine covalently conjugated to cellulose nanocrystals (CNC@ZnPc). Thin films of CNC@ZnPc sandwiched between two gold electrodes showed pronounced hysteresis in their current–voltage characteristics. The layered metal–organic–metal sandwich devices exhibit distinct high and low conductive states when bias is applied, which can be used to store information. Density functional theory results confirmed wave function overlap between CNC and ZnPc in CNC@ZnPc, and helped visualize the lowest (lowest unoccupied molecular orbital) and highest molecular orbitals (highest occupied molecular orbital) in CNC@ZnPc. These results pave the way forward for all-organic electronic devices based on low cost, earth abundant CNCs and metallophthalocyanines.